2022
DOI: 10.1155/2022/8762717
|View full text |Cite
|
Sign up to set email alerts
|

Targets and Potential Mechanism of Scutellaria baicalensis in Treatment of Primary Hepatocellular Carcinoma Based on Bioinformatics Analysis

Abstract: Objective. To analyze the target and potential mechanism of Scutellaria baicalensis (SB) in the treatment of HCC based on bioinformatics, so as to provide suggestions for the diagnosis, treatment, and drug development of hepatocellular carcinoma (HCC). Methods. The regulated gene targets of SB were screened by gene expression pattern clustering and differential analysis of gene expression data of HepG2 cells treated with SB at 0 h, 1 h, 3 h, 6 h, 12 h, and 24 h. The module genes related to HCC were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Studies have shown that SPAG5 serves a promising prognostic factor in HCC and acts as an oncogene [37][38][39][40]. Human centromere-associated protein (CENPE) can be used as potential biomarkers for clinical diagnosis [41]. CCNB1 and CCNB2…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SPAG5 serves a promising prognostic factor in HCC and acts as an oncogene [37][38][39][40]. Human centromere-associated protein (CENPE) can be used as potential biomarkers for clinical diagnosis [41]. CCNB1 and CCNB2…”
Section: Discussionmentioning
confidence: 99%
“…SPAG5 acts as an oncogene and is a promising prognostic factor in HCC [42][43][44][45]. Human CENPE are potential biomarkers for clinical diagnosis [46]. Cyclin B1 and CCNB2 are independent risk factors for HCC [47].…”
Section: Discussionmentioning
confidence: 99%